Inflation and finance - Botos, Katalin (Public Finance Quarterly, 2023)
The study concentrates on the discussion in Hungary about the causes of contemporary inflation: what are the main causes of it and how to rank them. It tries to establish whether the simple methods of monetary policy are appropriate to stop inflation. The method of the study is an overview of recent professional articles and the analysis of the data of Central Statistical Office publications. It concludes that the Hungarian inflation has several internal and external causes: uncovered spending power especially in time of the COVID epidemic, the growing energy prices because of the Ukrainian war, money retention for Hungary in Brussels, the inadequatetiming of monetary policy actions, the role of imbalance of payments and exchange rates evolution – direct and indirect impulses-, the role of inherited state debts and the accumulated wage distortions which is now to correct, and the tax policy which relies mainly on VAT. The conclusion of the study is that only by autonomous monetary policy actions cannot deal with inflation, because the national policy cannot get rid of the international money markets. It is time to change the tax policy for a more structured one relying on the progressive income taxes.